Novel Millet-Based Flavored Yogurt Enriched With Superoxide Dismutase - Fan, Xiankang; Li, Xiefei; Zhang, Tao; Guo, Yuxing; Shi, Zihang; Wu, Zhen; Zeng, Xiaoqun; Pan, Daodong (Frontiers in Nutrition, 2022)
Superoxide dismutase (SOD) is an important antioxidant enzyme with different physiological functions, which can be used as a nutritional fortifier in food. Cereal-based fermented products are becoming popular worldwide. In this study, novel millet-based flavored yogurt enriched with SOD was developed. Lactiplantibacillus plantarum subsp. plantarum was screened, which manufactured SOD activity of 2476.21 ± 1.52 U g−1. The SOD content of millet yogurt was 19.827 ± 0.323 U mL−1, which was 63.01, 50.11, and 146.79% higher than that of Bright Dairy Yogurt 1911, Junlebao and Nanjing Weigang, respectively. Fifty-four volatile flavor substances and 22,571 non-volatile flavor substances were found in yogurt. Compared to traditional fermented yogurt, 37 non-volatile metabolites in yogurt with millet enzymatic fermentation broth were significantly upregulated, including 2-phenyl ethanol, hesperidin, N-acetylornithine and L-methionine, which were upregulated by 3169.6, 228.36, 271.22, and 55.67 times, respectively, thereby enriching the sensory and nutritional value of yogurt. Moreover, the manufacture of unpleasant volatile flavor substances was masked, making the product more compatible with consumers' tastes.